Nutrition Status and Immunization as Determinant of Acute Respiratory Infection on Toddlers - Atira Atira (Humanistic Network for Science and Technology (HNST), 2017)
Acute Respiratory Infection (ARI) is one of infectious disease that is caused by micro bacteria or virus that can cause death to children in Indonesia in which the nutrition status and immunization become risk determinant factor. This research aimed to attain information about the nutrition status and immunization as a determinant of Acute Respiratory Infection (ARI) among toddlers (1-4 years old) in Bandung District, West Java, Indonesia. Analytical correlational survey was used in this research by using cross sectional scheme. Incidental sampling by having 94 respondents was used in this research. The data was analyzed by using univariate and bivariate along with Chi Square statistical test. The result showed that the nutrition status as a determinant of Acute Respiratory Infection (ARI) among toddlers with p-value 0.029, so Ho was rejected. Meanwhile, the status of immunization as a determinant of Acute Respiratory Infection (ARI) with p-value 0.005, so Ho was rejected. The nutrition status and immunization were determinant factors that caused Acute Respiratory Infection (ARI) among toddlers. Suggestion: health workers needed to improve preventive and promotive efforts in dealing with the demand of good nutrition status and the importance of complete immunization for infants so that toddlers were avoided from Acute Respiratory Infection (ARI), thus, they could grow well and normal. Keywords: Nutrition status, Immunization, ARI, Toddlers